Macroglossia Associated With Clobazam Administration: A Case Report and Literature Review - Zhang, Jeff F.; Nickerson, Kevin; Piryani, Ravi; Farooq, Osman; Swayampakula, Anil K. (Frontiers in Neurology, 2022)
Clobazam is a benzodiazepine derivative used as an antiepileptic agent for the treatment of focal and generalized seizures and drug-resistant epilepsy associated with Lennox-Gastaut Syndrome. While somnolence and mood-related side effects are commonly observed, acute macroglossia following initiation of Clobazam therapy has not been previously reported in the medical literature. In this case report, we present a female pediatric patient who developed significant tongue swelling with protrusion beyond the oral cavity after initiation of Clobazam for treatment-resistant epilepsy. Symptoms were unresponsive to antihistamines and steroids but resolved gradually in the days following discontinuation of Clobazam with no lingering sequelae.